Analysis of Handover Priority in Intra Technology Radio Access - Yuhanef, Afrizal; -, Zurnawita; Amalia, Fitri; -, Nasrul; Syawaldipa, Ardi (SOTVI, 2023)
A handover strategy is required to ensure connection continuity for cellular network users due to user mobility. Handovers on the same frequency (intra-frequency) and handovers on other frequencies (inter-frequencies) are conceivable in the Intra Radio Access Technology network. The network must be able to give the best quality and optimal bandwidth so that consumers can keep their connection. Most cells have more than one bandwidth channel. A test was performed in this study to determine the influence of priority handover on intra-frequency LTE handover on signal strength and throughput. This study is based on actual measurement findings from the deployed 4G LTE network transceiver device, which contains several carriers for each eNodeB. TEMS Pocket, a mobile gadget, was used to collect data for measurements. For analysis purposes, the parameters RSRP, throughput, frequency band, serving cell identification or PCI (Physical Cell Identity), and event handover are employed. In the inter-frequency LTE handover, there are two priority handovers: handovers from lower bands to higher bands (high priority) and handovers from higher bands to lower bands (low priority). When a low-priority handover happens, the RSRP value and throughput increase, while a high-priority handover causes the RSRP value to decrease.